Pengaruh Model Pembelajaran Probing Promting Terhadap Hasil Belajar Siswa pada Materi Sel pada Makhluk Hidup di Kelas XI IPA SMA Negeri 8 Buru Kecamatan Waplau - Muhamad Sehol (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study is to find out whether there is an influence of the promting probing learning model on student learning outcomes on the cell material of living things Class XI SMA Negeri 8 Buru This research was carried out at SMA Negeri 8 Buru class XI for the 2020/2021 school year. The samples used in this study were class X1 IPA2 as an experimental class and a control class. The data analysis technique used is a normality test, and a hypothesis test using the "t" formula. The research method used in this study is quantitative research. The results showed that the learning outcomes taught with the promting probing learning model were higher than the learning outcomes of students taught by conventional learning methods, namely lectures and questions and answers. The results of the statistical test showed that student learning outcomes with the probing promting learning model were pretests of 42.11 and postest of 78.42 while student learning outcomes using while the learning outcomes of students who use conventional learning methods are pretests of 42.11 and postest of hypothesis testing results obtained by thitung>ttabel, namely 0.00 at a significant level of 95% and α = 0.05. This means that the hypothesis in this study can be accepted and stated that there is a positive and significant influence of the influence of the promting probing learning model on student learning outcomes on class XI living matter cells at SMA Negeri 8 Buru